Benign Idiopathic Intracranial Hypertension with Empty Sella and Gonadotrophin Insufficiency - Hafeez, Nida; Gull, Nayab; Gull, Ambreen; Niazi, Fuad Ahmad Khan (Journal of Rawalpindi Medical College, 2026)
Background: Benign idiopathic intracranial hypertension (BIIH) is characterized by raised intracranial pressure without an identifiable intracranial pathology and commonly presents with headache. However, atypical presentations without headache may delay diagnosis and increase the risk of irreversible visual loss. Empty sella syndrome is a radiological finding that may be associated with raised intracranial pressure and pituitary dysfunction, though hormonal abnormalities are often under-recognized. Case Presentation: We report the case of a 38-year-old obese woman who presented with progressive visual impairment and asymmetric bilateral papilledema in the absence of headache, nausea, or vomiting. Visual acuity was preserved in the right eye but markedly reduced in the left eye. Neuroimaging revealed an empty sella with flattening of the pituitary gland, while cerebrospinal fluid opening pressure was markedly elevated. Hormonal evaluation demonstrated isolated gonadotropin insufficiency with low follicle-stimulating hormone levels. The patient was diagnosed with benign idiopathic intracranial hypertension associated with empty sella syndrome. Management included therapeutic lumbar puncture, oral acetazolamide, and combined estrogen–progesterone hormone replacement therapy initiated after endocrinology consultation. Gradual improvement in visual function was observed over a six-month follow-up period. Conclusion: This case highlights an atypical, headache-free presentation of benign idiopathic intracranial hypertension associated with empty sella syndrome and gonadotropin insufficiency. It underscores the importance of considering BIIH in patients presenting primarily with visual symptoms and emphasizes the role of comprehensive hormonal evaluation and multidisciplinary management in optimizing visual outcomes. Keywords: Idiopathic Intracranial Hypertension; Empty Sella Syndrome; Papilledema; Gonadotropin Deficiency; Visual Impairment.